Hungarian Counties and Regional development – Changing Roles in a Transforming Environment - István Hoffman (DETUROPE)
The main aim of this jurisprudential analysis is to review the transforming regulation and practice on the regional development tasks of the Hungarian county governments. The main European models of the regional (2nd or 3rd tier) municipalities will be reviewed by the article. Traditionally, the county municipalities have had an important role in the Hungarian public administration. The changing role of the counties in the development policies will be analysed, as well. Although this role was weakened after 1990, the new county governments have had significant service provider competences until 2011, but their development tasks were just partial. This system has been transformed by the new Hungarian Municipal Code. The counties lost the majority of their functions and they received competences in regional planning and development. These tasks were extended by the reforms between 2013 and 2016. These changes could be the base of a new “developer county” approach.